2018
DOI: 10.1016/j.joi.2017.12.005
|View full text |Cite
|
Sign up to set email alerts
|

On the relationships between bibliographic characteristics of scientific documents and citation and Mendeley readership counts: A large-scale analysis of Web of Science publications

Abstract: In this paper we present a first large-scale analysis of the relationship between Mendeley readership and citation counts with particular documents' bibliographic characteristics. A data set of 1.3 million publications from different fields published in journals covered by the Web of Science (WoS) has been analyzed. This work reveals that document types that are often excluded from citation analysis due to their lower citation values, like editorial materials, letters, or news items, are strongly covered and s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
33
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 56 publications
(79 reference statements)
5
33
0
1
Order By: Relevance
“…This phenomenon was also observed in non-scientific tweets; findings of Ferrara & Yang (2015) suggest that Twitter users are more inclined to share and favorite tweets with positive content. Our other results, with regard to title attractiveness, are in line with findings from (Zahedi & Haustein, 2018;Jacques & Sebire, 2010) who showed that publications that use colon in the title and have shorter titles are more likely to be downloaded from publisher website, to appear in (social) media and to receive citations. In addition, the PNAS publications in which a new person appears as co-author for the first time and holds the last authorship position attract more media attention than publications of scientists who publish frequently in PNAS and collaborate with diverse co-author teams.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…This phenomenon was also observed in non-scientific tweets; findings of Ferrara & Yang (2015) suggest that Twitter users are more inclined to share and favorite tweets with positive content. Our other results, with regard to title attractiveness, are in line with findings from (Zahedi & Haustein, 2018;Jacques & Sebire, 2010) who showed that publications that use colon in the title and have shorter titles are more likely to be downloaded from publisher website, to appear in (social) media and to receive citations. In addition, the PNAS publications in which a new person appears as co-author for the first time and holds the last authorship position attract more media attention than publications of scientists who publish frequently in PNAS and collaborate with diverse co-author teams.…”
Section: Resultssupporting
confidence: 91%
“…Title attractiveness. Zahedi & Haustein (2018) showed that Mendeley readership counts have a small negative correlation with the title length of paper in most disciplines. Publication titles with punctuation marks (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In the bottom-right quadrant in addition to the traditional bibliometrics (e.g. based on Scopus or Web of Science) and peer review, we also find F1000Prime recommendations and Mendeley readerships Mohammadi, et al, 2015;Zahedi, et al, 2014a;Zahedi & Haustein, 2018) both with a reasonably strong scholary focus (both are mostly used by scholars and are about scholary outputs), although they also have some social media focus (e.g. both are user generated and interactions among users and outputs are possible).…”
Section: Understanding the Nature Of Social Media Metrics For Researcmentioning
confidence: 65%
“…field and reputation of journals, open access) and document values (e.g. clinical value and basic value) (Bornmann, Schier, Marx, & Daniel, 2012;Zahedi & Haustein, 2018).…”
Section: Discussionmentioning
confidence: 99%